If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 2(x + -2) Reorder the terms: -5 + 4x = 2(x + -2) Reorder the terms: -5 + 4x = 2(-2 + x) -5 + 4x = (-2 * 2 + x * 2) -5 + 4x = (-4 + 2x) Solving -5 + 4x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 4x + -2x = -4 + 2x + -2x Combine like terms: 4x + -2x = 2x -5 + 2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 2x = -4 + 0 -5 + 2x = -4 Add '5' to each side of the equation. -5 + 5 + 2x = -4 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = -4 + 5 2x = -4 + 5 Combine like terms: -4 + 5 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| 2x=42/15 | | 0.2x+x=85 | | (1-2lnx)/x^3=0 | | 6c^6b^9/60c^6b^7 | | x^4-2x^3+7x^2-4x+10=0 | | 2^2x/3=1/16 | | 7x/14y | | (2c)+(C^2)=35 | | 2/n=8/20 | | (c^2)+(2c)=35 | | lnx^2=x | | 2*lnx^2=x | | 11(p-2)=8p+9+3zp | | 2x*lnx=x | | 8y-6=2(4y-3) | | F(x)=2x^4+cos^2x-3 | | 3w^2+24w+21=0 | | ((-8)/3)*((-14)-(-2)) | | 5*-8-16=3(2*-8-3)+1 | | L-9=5(5l-3) | | 3sin(2x/3)=2 | | 5x-16=3(2x-3)+1 | | 3(2x-1)=-39 | | 3-(2x+1)=3-2x-1 | | Y=xy-2x-4 | | x^2+(2+i)*x+2i=0 | | c^2=(5c)/4 | | 3x-26=4(x-5) | | x(x^2)=8 | | x(x^2)=9 | | 3l-2=5(3l-3) | | x(x^2)=40 |